Repetitive transcranial magnetic stimulation increases serum brain-derived neurotrophic factor and decreases interleukin-1β and tumor necrosis factor-α in elderly patients with refractory depression. Issue 5 (May 2019) - Zhao, Xiangxiang; Li, Yanpeng; Tian, Qing; Zhu, Bingqian; Zhao, Zhongxin
Objective: To investigate the effects of repetitive transcranial magnetic stimulation (rTMS) on serum levels of brain-derived neurotrophic factor (BDNF), interleukin (IL)-1β, and tumor necrosis factor (TNF)-α in elderly patients with refractory depression. Methods: A total of 58 elderly patients diagnosed with refractory depression between January 2015 and December 2016 were divided randomly into two groups: 29 patients who received rTMS and 29 controls without rTMS. Thirty healthy individuals were also enrolled and all received rTMS. Serum levels of BDNF, IL-1β, and TNF-α were measured before the study (0 days), and at 48 hours and 1, 2, 3, and 4 weeks after the first TMS treatment. Results: BDNF levels gradually increased with treatment duration in the rTMS group and were significantly higher compared with the control group. In contrast, IL-1β and TNF-α levels gradually decreased and were significantly lower than in the control group. None of the serum factors were affected by rTMS in the healthy individuals. BDNF levels were negatively correlated and IL-1β and TNF-α levels were positively correlated with Hamilton Depression Rating Scale-24 scores. Conclusion: These results suggest that rTMS may increase BDNF and decrease IL-1β and TNF-α serum levels in elderly patients with refractory depression.